The presence of masks in the female initiation ritual of the Tikuna people (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
In this article, the research on Tikuna Amerindian masks, located on the triple borderbetween Brazil, Colombia and Peru, will be addressed. It is a theoretical-practical research, usingthe methodology of autoetnographic research, where the artist's gaze is evident. So, from mycoexistence with the Tikuna, in the village (in Nossa Senhora de Nazaré, AM) and in an urbancontext (in Parque das Tribos, Manaus) I will talk about this universe of masks that are part of themain Tikuna ritual, of female initiation Worecü, The Feast of the Young Girl, which happens whenthe girl Tikuna has her menarche.